The Relationship Between Information Access And Traders' Behavior In The Use Of Formalin And Boracx In School Children's Snacks - Rizky Amalia Nur’aini; Windi Wulandari (JURNAL KESMAS DAN GIZI (JKG), 2025)
Food safety is one of the important issues in public health that affects quality of life, especially for children as the main consumers of school snacks. In this study, formalin and borax were still found in elementary school snacks. The purpose of this study was to analyze the relationship between access to information and the behavior of vendors regarding the use of formalin and borax in snacks sold around elementary schools in the Laweyan area, Surakarta. The research method used a quantitative observational analytical approach with a cross-sectional design, This study used a questionnaire and conducted tests in a microbiology laboratory. The sample consisted of 75 snack vendors selected using total sampling. Data were collected through a questionnaire that had been tested for reliability and validity. The findings revealed that a p-value of <0.05 indicated a statistically significant impact of information access on vendors' behavior. Additionally, the Prevalence Odds Ratio (POR) of 7.543 with a 95% confidence interval (CI) of (2.262–25.149) showed that vendors with good access to information contributed to the use of harmful food additives. Adequate knowledge and education are crucial for changing traders' behavior to prioritize food safety. This study is expected to serve as a reference for enhancing awareness and oversight regarding the use of safe food additives.